Structure and properties of Li ferrite synthesized from Fe2O3–Li2CO3–Sm2O3 powders - E. N. Lysenko; V. A. Vlasov; Yu. S. Elkina; A. P. Surzhikov (Тонкие химические технологии, 2025)
Objectives. To study the structure and properties of lithium ferrites obtained by preliminary solid-phase synthesis of samples based on Fe2O3-Li2CO3-Sm2O3 powder mixtures having various concentrations of samarium oxide (0, 4.7, and 14.7 wt %) at 900°C and their subsequent high-temperature sintering at 1150°C.Methods. The structural and morphological characteristics of the synthesized and sintered samples were studied by X-ray powder diffraction analysis, scanning electron microscopy, thermogravimetric analysis, and differential scanning calorimetry.Results. The preliminary synthesis gives a two-phase composite structure containing unsubstituted lithium ferrite Li0.5Fe2.5O4 having a spinel structure and a perovskite-like SmFeO3 phase. An increase in the Sm2O3 content from 4.7 to 14.7 wt % in the initial Fe2O3-Li2CO3-Sm2O3 mixture leads to an increase in the amount of the secondary SmFeO3 phase in the synthesized samples from 4.9 to 18.2 wt %. The high Curie temperature values (631–632°C) and obtained values of the enthalpy of the a→b phase transitions in lithium ferrite indicate that the main product in all synthesized samples is the ordered a-Li0.5Fe2.5O4 phase. Subsequent sintering at elevated temperatures leads to a decrease in the SmFeO3 phase content to 3.8 and 16.5 wt % and to an increase in the content of the lithium ferrite phase. The sample not modified with samarium contains a significant amount of the disordered b-Li0.5Fe2.5O4 phase, as confirmed by the reduced values of the Curie temperature and phase transition enthalpy. The density of such a sample is 4.4 g/cm3. The introduction of samarium ions leads to the preservation of the ordered a-Li0.5Fe2.5O4 phase during sintering. The density of the sintered samples decreases to 4.3 and 4.1 g/cm3 with an increase in the concentration of samarium oxide introduced at the synthesis stage to 4.7 and 14.7 wt %, respectively.Conclusions. The introduction of samarium oxide to low concentrations (up to 4.7 wt %) during ferrite synthesis leads to the formation of a two-phase composite structure during sintering, which mainly consists of an unsubstituted lithium ferrite phase having more regular polyhedral grains and a low content of the secondary perovskite-like phase. The formation of the secondary phase, whose properties differ from those of ferrite, along with the characteristics obtained for such samples, which include a slight decrease in density while maintaining a high Curie temperature corresponding to the main magnetic phase, make ferrites modified with low concentrations of rare earth elements promising for further study of their electromagnetic properties in the microwave range.